Efficiency of different doses of phosphorus, zinc, and molybdenum applied via seed treatment on the quality of maize seeds (Research, Society and Development, 2025)
Brazil stands out in the global agricultural sector and ranks among the top three maize producers. However, despite high yields, one of the factors that significantly reduces production is plant nutritional imbalance. Deficiencies in macro- and micronutrients such as phosphorus (P), zinc (Zn), and molybdenum (Mo) can lead to considerable losses in maize yield. This study aimed to evaluate the effect of adding P, Zn, and Mo via seed treatment, in seeds with different initial vigor levels, on maize seed physiological quality. The experiment was conducted in a completely randomized design with eight analytical replications, using the cultivar IAC 8077 (Agronomic Institute, S1 category). Treatments consisted of combining nine doses of a formulation containing P, Zn, and Mo (0, 50, 100, 150, 200, 250, 300, 350, and 400 mL per 100 kg of seeds) with two initial vigor levels (high and low), in a 9 × 2 factorial arrangement, totaling 18 treatments. Physiological quality was assessed using standard germination, accelerated aging, modified cold test, seedling emergence in sand, and field emergence. The best physiological potential results were obtained with a dose of 50 mL per 100 kg of seeds in the formulation containing P, Zn, and Mo, especially in high-vigor seeds. The different doses did not cause phytotoxicity symptoms in the resulting seedlings.